The Status of Wildlife Environmental Conservation in Oba Hills National Park, Nigeria (2021)
This study focused on the major threats to the natural environment and wildlife conservation in Oba Hill National Park (OHNP), Osun State, Nigeria. It investigated the management measures such as anthropogenic and land use activities for the protection of wildlife resources in OHNP. The study was conducted by means of surveying and monitoring the buffer zone area of OHNP between October 2015 and April 2016. Data were collected with the aid of structured questionnaire administered in five (5) purposively chosen sites for sampling based on their proximity to the park. A total of 100 respondents were selected randomly from the surrounding villages at 20 respondents per site. It was observed that majority of respondents were males (65%), married (67%), were Islamic (50%), were hunters (25%), within ages 41-50 years (38%) and had primary/secondary school education (68%). Majority took hunting as a secondary activity (65%), used short guns (47%) and hunted Bushbuck (30%) via individual hunting (58%). On farming activities, majority of the respondents practiced subsistence farming (55%), using manual land preparation methods (75%) and responded that farming did not have any effect on wildlife resources (65%). Majority of respondents indicated that bushfire was caused by deliberate (67.4%) anthropogenic activities (75%), such as vegetation clearing (65%) as deliberate source and dropping of cigarette butts (72.7%) as accidental source of bushfire. They reported there were attempts to control the fire (86.4%) and the bushfires did not have any form of benefit to them (76%).The problems identified from the study area were habitat destruction through uncontrolled logging, agricultural projects, highway and urban development, exploitation for fuel wood, over hunting and poaching. Management strategies necessary for adoption for wildlife protection is the upgrade of the forest reserve to a national park status, enactment of wildlife laws, signing of international treaties and manpower development.